PENGARUH PEMANFAATAN MAGGOT (Hermetia illucens) DARI LIMBAH BUNGKIL KELAPA SAWIT SEBAGAI PAKAN ALTERNATIF TERHADAP PERTUMBUHAN IKAN LELE (Clarias batrachus L) - Yasi Ririzky; Rivo Yulse Viza; Andriyanto (BIOCOLONY, 2021)
The lack of utilization of palm oil cake waste in Merangin Regency has become a source of pollution. Palm oil cake waste has the potential as a medium for Hermetia illucens production. This study aims to determine the effect of using Hermetia illucens from palm oil cake waste as an alternative feed on the growth of Clarias batrachus L and to determine the best dose of feed from oil palm cake waste Hermetia illucens on the growth of Clarias batrachus L . This study use a completely randomized design (CRD) factor, consisted of 5 treatments, P A (100% Pellet/control), P B (25% Hermetia illucens and 75% pellets), P C (50% Hermetia illucens and 50% pellets) , P D (75% Hermetia illucens and 25% pellets), and P E (100% Hermetia illucens ) with 5 repetitions. The parameters of this study were weight growth, body length growth, and water pH. Data were analyzed using analysis of variance and continued with Duncan's test 5%. The results showed that Hermetia illucens feed from palm oil cake waste had a significant effect on the growth of body weight and body length in catfish. Hermetia illucens feed from palm oil cake waste at a dose of 50% Hermetia illucens & 50% pellets gave the highest results on the growth of body weight and body length in Clarias batrachus L.